Change of Graphene with Various Strategies for Photocatalytic Applications: A Review - Whon Chun Oh (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2020)
Because of its novel molecular 2D structure and momentous physicochemical properties, graphene has been started a whirlwind of the investigation into its optical, electronic, thermal, and mechanical properties. Specifically, a lot of considerations have been pulled in to investigate graphene and graphene composites for photoelectrochemical applications. Many works have been done to synthesize novel graphene-based materials for applications in photoelectrochemistry, such as photoelectrochemical sunlight-based cells, photocatalytic disintegration of natural contaminations, and H2 production. In this article, we abridge the condition of research on graphene-based materials for photoelectrochemistry. The prospects and further improvements in this energizing field of graphene-based materials are additionally discussed. A B S T R A KKarena struktur 2D dan keunggulan karakteristik fisika-kimia, graphene telah mulai diselidiki secara menyeluruh terhadap sifat optik, elektronik, panas, dan mekanik. Secara khusus, focus dipelukan untuk menyelidiki graphene dan komposit graphene untuk aplikasi fotoelektrokimia. Banyak studi dikerjakan untuk membuat material baru berbasis graphene untuk aplikasi fotoelektrokimia seperti photoelectrochemical sunlight-based cells, fotokatalitik untuk penghilangan kontaminan, dan produksi H2. Pada artikel ini akan disumarisasikan penelitian-penelitian terkait material berbasis graphene untuk aplikasi fotoelektrokimia. Harapan dan perkembangan aplikasi penggunaan material berbasis graphene juga didiskusikan.